Why you do not have to do any computing or math do solve 15 x 0 x (13 + 7)? Explain.

Answers

Answer 1
Answer:

Answer:

because when you do 15*0 it =0 so anything else multiplied by 0 is 0

Step-by-step explanation:


Related Questions

What is the ratio of consonants to vowels in the english language?
Find the area and circumference of a circle with diameter 8yd
PLEASEEEEEEEE HELPPPPPPPPPPPPPPPPPPPPPPPP MEEEEEEEEEEEEEEEEEEEE
Express 4-3i/(1+i)(2-3i) in the a+bi form
Consider the quadratic function f(x) = -x²-x+2.Determine the following: (enter all numerical answers as integers, fractions, or decimals): The x-intercepts are The y-intercept is The vertex is The line of symmetry has the equation Give your answers as points, separated by a comma. Give your answer as a point.

Fill in the common equivalents. 1.) 66 2/3%
= ?/?

Answers

well 66 is 66 and 2/3 is 66.6 repeating so 66 

What multiplies to 6 and adds to 13

Answers

The Answer would be 3 

3x2=6 
10+3=13

Answer what you can pleases

Answers

I just wrote the answers on the picture.

Find f(-11/5) if f(n) = 5n + 6.. A) -17. B) 5. C) -6

Answers

f(n)=5n+6\n\nf\left(-(11)/(5)\right)=?\n\nsubtitute\ n=-(11)/(5)\ to\ the\ equation:\n\nf\left(-(11)/(5)\right)=5\cdot\left(-(11)/(5)\right)+6=-11+6=-5
f(-11/5)=5(-11/5)+6
f(-11/5) = -11+6
f(-11/5) = -5 so option B is correct

Solve ry + s = tx - m for y. Explain each step in your solution?A. Would there be any limitations for the value of each variable? If so, explain the limitation?

Answers

Let's solve for mry+s=tx-mstep 1: Flip the equationstx-m=ry+sstep 2: Add -tx to both sidestx-m+(-tx)=ry+s+(-tx)-m=ry-tx+sstep 3 :Divide both sides by -1-m-1=ry-tx+s-1m=-ry+tx-sI hoped i help :)

2. There are 3 apples and 5 oranges in a bag. Determine the probability of selecting anorange, then an apple when they are chosen at random without replacement.

Answers

Because of their consistency? That’s the only thing that came to my mind